Potential Endophytic Fungi from the Leaves of Syzygium zeylanicum (L.) and Their Secondary Metabolite - Elfita, Elfita; Syarifah, Syarifah; Widjajanty, Hary; Setiawan, Arum; Kurniawati, Alfia Rahma (Universitas Jenderal Soedirman, 2023)
Endophytic fungi coexist without harms in the host in some parts or all parts of its lifecycle. Endophytic fungi excrete specialized bioactive compounds beneficial for of its host; the compound itself can be different from what can be found on their host. Endophytic fungi are capable to excrete biologically significant secondary metabolites acting as antidiabetic, antioxidant, antimicrobial, and cytostatic agents. Endophytic fungi existence are common across different plants; including Syzygium zeylanicum that can be found in Indonesia. This study aims to isolate endophytic fungi found in leaves of Syzygium zeylanicum, L., to elucidate their characterized morphologically, and to examine its antimicrobial and antioxidant properties in addition to their chemical structures. Characterization of endophytic fungi was conducted by their macroscopic and microscopic features, followed by molecular characterization of highly bioactive metabolites. Antimicrobial activities were measured by disc diffusion method. Antioxidant properties were measured with DPPH. Secondary metabolites were chromatographically isolated and identified with spectroscopy techniques (NMR ID and 2D). Four endophytic fungi isolates were obtained: Penicillium citrinum (SZ1), Colletotrichum lindemuthianum (SZ2), Aspergillus nidulan (SZ3), Scopulariopsis asperula (SZ4). Penicillium citrinum (SZ1) showed antimicrobial activities against four different bacteria (71.3% against E. coli; 74.1% against S. aureus; 76.2% against S. typhi; and dan76.9% against B. subtilis). Antioxidant activity ini all ekstrak of endophytic fungi showed very activity (IC50 SZ3 extract = 3.85 µg/mL). Potential endophytic fungi SZ1 was molecularly identified as Penicillium citrinum. Extracts from SZ1 fungi contains bioactive 4-hydroxy-2-(4-hydroxyphenyl)-ɣ-butyrolactone-3-yl) methyl acetate. The newly obtained substance could be developed into antimicrobial and antioxidant agents in further studies.